Hubungan Motivasi Belajar dengan Prestasi Belajar Matematika Siswa Kelas V SD Negeri Daerah Binaan 1 Sumbang Banyumas - Suharti, Suharti; Muslim, Arifin; Sriyanto, Sriyanto (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2020)
This researched is aimed to discover the relationship between learning motivation and learning achievement of mathematics subject for 5 graders in Fostered Public Primary School 1 sub-district Sumbang, Banyumas. The methods used for this research was corelation with quantity approach. The population was 387 students of grade V from 11 public primary schools, while 197 students were used for sampling. The samples were collected using probability sampling. The technique used for data collection were a non-test technique in form of learning motivation Â questionnaire and a test technique in form of essay questions. The result of this research shows that there is a relationship between learning motivation and learning achievement with rhitungrtabel = 0,3490,1398 with significance value 0,0000,05, so it is said as significant and applicable to the population. Regression test result shows that Y` = a + bX with the value of a = 7,861, which means if learning motivation = 0, so learning motivation = 7,861.Â The coeficient of b = 0,611, which means if learning motivation is raised up to 1 denomination, so learning motivation will be raised up to 0,611 denomination as well. These datas show that if the value of X is raised, the value of Y will be raised as well for both of them has positive and same direction of relationship.